PELUANG DAN TANTANGAN PENDIDIKAN AGAMA ISLAM DI ERA ARTIFICIAL INTELLIGENCE - Noor, Hasni; Muhdi, Muhdi; Nashrulloh Kartika MR, Galuh; Herlinawati, Herlinawati (Penerbit Lafadz Jaya, 2025)
This study aims to identify the opportunities and challenges in integrating AI into PAI learning and to formulate effective strategies for its utilization. The research employs a literature review method with a descriptive-qualitative approach. The results reveal that AI offers opportunities such as personalized learning, increased accessibility, support for students with special needs, and professional development for teachers. However, challenges also arise, such as the potential erosion of spiritual values, technological dependency, and limited digital literacy among educators and students. Therefore, a wise integration strategy is required so that the use of AI is not only technically effective but also aligned with Islamic values.